Transformation includes moving a shape from its original position.
-
The sequence of transformation from X to Y is: reflection across the y-axis, and then a 1 unit left translation
- The transformation mapping is: [tex](x,y) \to (-x -1,y)[/tex]
(a) Sequence of transformation
From the graph, we observe that
-
Figure X is reflected across the y-axis
- Then shifted to the left
(b) Transformation mapping
Represent the coordinate of X with [tex](x,y).[/tex]
The rule of the first transformation, when reflected across the y-axis is
[tex](x,y) \to (-x,y)[/tex]
The rule of the second transformation, when shifted 1 unit left is:
[tex](x,y) \to (x - 1,y)[/tex]
This gives:
[tex](-x,y) \to (-x - 1,y)[/tex]
Hence, the transformation mapping is:
[tex](x,y) \to (-x - 1,y)[/tex]
Read more about transformations at:
brainly.com/question/11707700